Kinerja Pengelolaan Dana Desa: Dampak Partisipasi, Evaluasi Anggaran, dan Kejelasan Tujuan - Anastasia Wea; Sari Rahmadhani (Owner : Riset dan Jurnal Akuntansi, 2025)
Effective and transparent management of village funds is an important factor in improving the performance of village apparatus and ensuring targeted budget allocation. However, challenges such as low community participation, less optimal budget evaluation, and unclear budget goals are still obstacles to managing village funds. This study seeks to examine the impact of budget participation, budget evaluation, and budget objective clarity on the performance of the village fund management apparatus in Aesesa District, Nagekeo Regency, NTT. This study employs a quantitative approach using a survey method, distributing questionnaires to 103 respondents who are part of the village fund management apparatus. Data analysis uses multiple linear regression. The study results indicate that budget participation, budget evaluation, and budget objective clarity have a positive and significant impact on the performance of the village fund management apparatus. Greater community participation in the budgeting process enhances the transparency and accountability of village fund management. Budget evaluations carried out systematically can increase the effectiveness of budget use and minimize potential deviations. Meanwhile, the clarity of budget goals makes it easier for the apparatus to achieve the established goals, their performance must be optimized. This study concludes that enhancing budget participation, budget evaluation, and budget objective clarity can directly develop the performance of the apparatus in managing village funds. These findings contribute to village governments in improving financial governance that is more transparent, accountable, and oriented towards community welfare.